COVID 19 and vaccine safety - Przemysław Raczkiewicz; Bartłomiej Zaremba; Natalia Śmiech; Katarzyna Nowakowska; Martyna Lewkowicz; Marcin Trojnar (Kazimierz Wielki University, 2021)
Introduction. COVID-19 disease, caused by SARS-CoV-2 virus, has been recognised as pandemic by WHO since March 11, 2020. It has been estimated that the disease is responsible for the death of 3.11 million people worldwide. Although several therapeutic agents have been evaluated for the treatment of COVID-19 disease, vaccines are considered to be the safest form of protecting patients against COVID-19. The safety of each vaccine is vital to control the pandemic. Due to the fact that vaccines have been launched quite recently and their production technologies are different, the safety of each preparation should be looked into separately. Nucleic acids do not trigger such a strong immune response on their own as viral vectors and that is why mRNA vaccines seem to be the safest types of vaccines. In December 2020, after a year since detecting the first case of by SARS-CoV-2 infection in humans, the first anti-COVID-19 vaccine became available. Objective. The purpose of this review was to present the literature data and the latest recommendations on risks related with COVID-19 vaccines. Method. The latest literature was reviewed based on PubMed and Google Scholar databases, using the following keywords: COVID-19; vaccines; safety Conclusions. Anti-COVID-19 vaccines seem not to cause many adverse events and side effects such as fever, chills, muscle pain, headache and fatigue. These are not serious and subside after taking over-the-counter pain relievers. Currently, there are no information on safety and efficacy of vaccines in pregnant and breast-feeding women, international expert recommendations leave the decision about vaccination with a woman, who should previously consult the benefits and risks involved with her doctor.